The development and significance of foreign trade in agri-food products in selected preferential trade agreements - Pawlak, Karolina (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2013)
The aim of the paper is to present the development tendencies and the significance of agri-food trade in selected preferential trade agreements in both Americas, Asia and Africa. The analysis included the values of trade turnover both within the region and in exchange with third countries, the share of the agri-food trade in the total trade in the region and the share of the regions under investigation in the global agri-food trade. The analysis allowed us to indicate the greatest global exporters and importers of agri-food products. The assessment of trade creation and trade diversion effect in agri-food trade of selected trade agreements was also possible.